Sexuality and new religious movements - Bogdan, Henrik; Lewis, James R. (Palgrave studies in new religions and alternative spiritualities, 2014)
This anthology brings together leading scholars in the field of New Religious Movements to critically investigate the role of sexuality in some of the most well-known new religious movements